2022
DOI: 10.1186/s13148-022-01321-8
|View full text |Cite
|
Sign up to set email alerts
|

JIB-04, a histone demethylase Jumonji C domain inhibitor, regulates phenotypic switching of vascular smooth muscle cells

Abstract: Background Vascular smooth muscle cell (VSMC) phenotype switching is critical for neointima formation, which is the major cause of restenosis after stenting or coronary artery bypass grafting. However, the epigenetic mechanisms regulating phenotype switching of VSMCs, especially histone methylation, are not well understood. As a main component of histone lysine demethylases, Jumonji demethylases might be involved in VSMC phenotype switching and neointima formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The proliferation and migration of stimulated VSMCs would be accompanied by a phenotypic switching of VSMCs from a contractile to a synthetic phenotype. 17,18 To clarify the role of galangin in phenotypic switching of VSMCs, we performed immunofluorescence assays on VSMCs in different subgroups to evaluate the expressions of the phenotypic switching related marker proteins α-SMA, SM22α and OPN. The results show that galangin suppressed the PDGF-BB induced expression of OPN; however, it promoted the expressions of α-SMA and SM22α induced by PDGF-BB, as shown in Fig.…”
Section: Galangin Restrained Pdgf-bb-induced Phenotypic Switching Of ...mentioning
confidence: 99%
“…The proliferation and migration of stimulated VSMCs would be accompanied by a phenotypic switching of VSMCs from a contractile to a synthetic phenotype. 17,18 To clarify the role of galangin in phenotypic switching of VSMCs, we performed immunofluorescence assays on VSMCs in different subgroups to evaluate the expressions of the phenotypic switching related marker proteins α-SMA, SM22α and OPN. The results show that galangin suppressed the PDGF-BB induced expression of OPN; however, it promoted the expressions of α-SMA and SM22α induced by PDGF-BB, as shown in Fig.…”
Section: Galangin Restrained Pdgf-bb-induced Phenotypic Switching Of ...mentioning
confidence: 99%
“…These studies on histone methylation were conducted mostly in the context of cancer and degenerative diseases, which have been shown to be closely affected by ferroptosis. Interestingly, the findings of our group and others have suggested that multiple forms of regulated cell death are involved in the development of aortic dissection (AD), and histone methylation plays a critical role in these biological processes 83,90–95 . More importantly, our recently published results revealed that ferroptosis, in particular, is involved in the development of AD 96 .…”
Section: Epigenetic Regulation In Ferroptosismentioning
confidence: 78%
“…Interestingly, the findings of our group and others have suggested that multiple forms of regulated cell death are involved in the development of aortic dissection (AD), and histone methylation plays a critical role in these biological processes. 83,[90][91][92][93][94][95] More importantly, our recently published results revealed that ferroptosis, in particular, is involved in the development of AD. 96 Furthermore, by screening multiple inhibitors of methyltransferases, we found that BRD4770 negatively regulated ferroptosis in VSMCs by inhibiting the H3K9me1/2/3 modifications.…”
Section: Histone Methylation In Ferroptosismentioning
confidence: 81%
“…Numerous studies have shown that inhibition of autophagic flux can lead to vascular injury, for example by inhibiting the proliferative migration and contractile phenotype of HAVSMCs, as well as increasing vascular senescence and calcification [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%